Rancang Bangun Sistem Pompa Elektrik Oli Mesin Berbasis IOT - Unggul, Pamungkas; Kurniawan, Edy; Intan Vidyastari, Rhesma (SinarFe7, 2025)
Manual operation of engine oil pumps is often prone to inaccuracy and requires continuous human supervision. Furthermore, the reliance on electricity from conventional sources increases operational costs and may result in suboptimal energy efficiency. This study presents the design and development of an Internet of Things (IoT)-based electric engine oil pump system capable of automatically controlling and monitoring oil volume in real time. The proposed system utilizes an ESP8266 NodeMCU Lolin V3 as the primary microcontroller, integrated with a flowmeter, 4×4 keypad, relay, and electric pump. For remote operation, the system employs the Blynk application over a Wi-Fi network. The research methodology encompasses hardware and software development, followed by performance evaluation based on predefined input codes (*123#, *456#, and *789#) and remote control via the Blynk platform. Experimental results demonstrate that the system can dispense oil with high precision, achieving an average measurement deviation of only ±5 mL. Moreover, the system supports remote operation and enables automated data logging to an online spreadsheet, thereby enhancing operational efficiency and data accessibility